Réponses

2014-06-17T08:08:11+02:00
F) x+1 =1                  
       4    2
4x/4 = - 1/4 + 2/4
4x/4 = 1/4
4x = 1
x = 1/4

i) 2(x-5)=3(-x+2)
2x - 10 = - 3x + 6
2x + 3x = 6 + 10
5x = 16
x = 16/5

k) -2  (x+3)- 1 3 x - 1     
     3           2       4   
 2-2/3x - 6/3 - 1/2 = 3/4x - 1/2
-2/3x - 3/4x = 6/3 + 1/2 - 1/2
-8/12x - 9/12x = 24/12
- 17x - 4x = 24
- 17x = 24
x =  - 24/17

m) x-(5-3x)=3x+4x
x - 5 + 3x = 3x + 4
x + 3x - 3x = 5 + 4
x = 9

l) -3x   = 
    2       2
- 3x = 7
x = - 7/3


pour m j'ai fait une erreur x-(5-3x)=3x+4
x-5+3x = 3x+4 4x-5 = 3x+4 4x-3x = 5+4 x = 9 JE PEUX pAS EDITER, je l'ai signalé on m'a jamais repondu!!!!!!!!!!!!
maudmarine erreur d'enoncé m) x-(5-3x)=3x+4x